2007
DOI: 10.1002/jcu.20351
|View full text |Cite
|
Sign up to set email alerts
|

Lower blood flow velocity, higher resistance index, and larger diameter of extracranial carotid arteries are associated with ischemic stroke independently of carotid atherosclerosis and cardiovascular risk factors

Abstract: Stroke patients in acute as well as chronic stable phase appeared to have larger CCA diameters, lower carotid flow velocities and volume, and higher resistance index than nonstroke patients independently of extracranial carotid atherosclerosis. These findings need to be confirmed by a prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 32 publications
(41 reference statements)
6
63
1
1
Order By: Relevance
“…Aging, cerebrovascular risk factors, and stroke status are associated with larger cross-sectional areas and slower, more pulsatile blood velocity within the large arteries. 12,13 Such changes occurring in proximity to the ASL labeling plane may confound CBF quantification in these clinical cohorts. For instance, age is associated with a decreased signal-to-noise ratio, due, in part, to increased variance between individual control-tag difference images.…”
mentioning
confidence: 99%
“…Aging, cerebrovascular risk factors, and stroke status are associated with larger cross-sectional areas and slower, more pulsatile blood velocity within the large arteries. 12,13 Such changes occurring in proximity to the ASL labeling plane may confound CBF quantification in these clinical cohorts. For instance, age is associated with a decreased signal-to-noise ratio, due, in part, to increased variance between individual control-tag difference images.…”
mentioning
confidence: 99%
“…Our previous casecontrol study showed that end-diastolic velocity (EDV), peak systolic velocity (PSV), and resistive index (RI) measured in carotid artery were associated with IS. 9 Among these, EDV, a potential marker of intracranial resistance, 9 was most significant. Nevertheless, EDV was not studied before.…”
mentioning
confidence: 99%
“…Therefore, improvement in diastolic velocity may protect the patient from ischemic stroke as it keeps adequate blood flow during diastole. Pulsatility index and resistive index may reflect the compliance of the vessel and therefore, high PI and/or RI may indicate increase vascular resistance and increase in arterial stiffness [15,16]. Previous studies showed that diabetic patients have higher resistive index than normal population and this may increase micro-and macro-vascular complications [32].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in resistive index means decrease in compliance of artery and atherosclerosis [13]. Increase in pulsatility index means reduction in perfusion of cerebral tissue [14][15][16]. Metformin is the only member of the biguanide group of oral anti-diabetic drugs available for use today.…”
Section: Introductionmentioning
confidence: 99%